Preparation of monopodal and bipodal aluminum surface species by selective protonolysis of highly reactive [AlH3(NMe2Et)] on silica. Issue 35 (22nd August 2017) - Sauter, D. W.; Chiari, V.; Aykac, N.; Bouaouli, S.; Perrin, L.; Delevoye, L.; Gauvin, R. M.; Szeto, K. C.; Boisson, C.; Taoufik, M.
Abstract : The reaction of [AlH3 (NMe2 Et)] with silica treated at 200 °C leads to a well-defined bipodal aluminum hydride while with silica treated at 700 °C a mixture of mono- and bi-podal aluminum hydrides is obtained. Abstract : The synthesis and characterization of silica-grafted monopodal and bipodal aluminum hydrides has been achieved starting from 200 °C- and 700 °C-annealed silica and [AlH3 (NMe2 Et)]. The mechanism by which aluminum trishydride reacts with isolated and vicinal silanols, assisted by the amine, has been investigated computationally at the ωB97XD-DFT level.